"The righteous shall inherit the Land, and live in it forever" (Ps. 37:29). Towards a theology of and human and divine justice through the reception history of Psalm 37 - Gillingham, S (Vandenhoek and Ruprecht, 2019)
The roots of this paper go back to a conference held at Worcester College, Oxford, in 2010, entitled ‘Conflict and Convergence: Jewish and Christian Approaches to the Psalms’. At that conference the summation paper was given by Frank-Lothar Hossfeld: its title was ‘Problems and Prospects in Psalter Studies’. There Hossfeld compared the Psalter to a house of many rooms, and this three-dimensional view allowed him to look at the theology of the Psalter in terms of adjoining psalms, twin psalms, psalms with similar titles, psalms connected by formulae such as הללויה and הודו, and psalms connected by themes such as ‘God is King’. This metaphor also allowed for the emphasis on the ספר תהלים as a unified scroll, comprising many psalms connected together in many different ways, all with their different histories of reception. The theology of the Psalter, the key theme in this publication, is about ‘diversity in unity’, and what follows with respect to the reception history of Psalm 37 is an exploration of the implications of this.